Controlled release fertilizers for sustainable agriculture - Lewu, F. B.; Volova, Tatiana G.; Thomas, Sabu; Rakhimol K. R. (Academic Press, 2021)
Controlled Release Fertilizers for Sustainable Agriculture provides a comprehensive examination of precision fertilizer applications using the 4-R approach--the right amount of fertilizer at the right time to the right plant at the correct stage of plant growth. This volume consolidates detailed information on each aspect of controlled release fertilizers, including up-to-date literature citations, the current market for controlled release fertilizers and patents. Presenting the tremendous advances in experimental and theoretical studies on sustainable agriculture and related areas, this book provides in-depth insight into state-of-the-art controlled release mechanisms of fertilizers, techniques, and their use in sustainable agriculture. Conventional release mechanisms have historically meant waste of fertilizers and the adverse effects of that waste on the environment. Controlled release delivery makes significant strides in enhancing fertilizer benefit to the target plant, while protecting the surrounding environment and increasing sustainability.